Faramarz, the Sistani hero : texts and traditions of the Faramarzname and the Persian epic cycle - Zutphen, Marjolijn van (Marjolijn Elisabeth), 1973- (Studies in Persian cultural history., 2014)
In Farāmarz, the Sistāni Hero, Marjolijn van Zutphen discusses the manuscripts, storylines and main themes of the shorter and the longer Farāmarznāme (c. 1100), in relation to Ferdowsi's Shāhnāme and several other later maṡnawis about the warriors from Sistān (the Persian Epic Cycle). Farāmarz, a secondary figure of the Shāhnāme, gained importance in later epic traditions and as the invincible protagonist of both Farāmarznāmes reached a status that equalled, if not surpassed, that of his famous father Rostam. Van Zutphen further shows how Farāmarz displays parallels to the fictional figures of Garshāsp (his ancestor) and Eskandar and argues that some story elements of Farāmarz's Indian conquest may be rooted in historical events from both the Parthian and the Ghaznawid period.